Global Talent Management through a Daoist Lens: Reframing Diversity, Merit, and Human Excellence across Cultural Contexts—A Systematic Review - Shahrukh Asif Khan; Arya Girija Bhuvanendran (Journal of Daoist Studies, 2026)
Background: Global Talent Management (GTM) operates within an era of intensifying institutional divergence, wherein organizations must simultaneously navigate equity-oriented DEI mandates and performance-driven merit imperatives. Since 2020, regulatory realignments including EU mandatory diversity reporting frameworks and politicization of DEI in the United States have deepened the equity-merit tension in organizational talent systems. Despite growing scholarly interest, no systematic study has theorized how institutional contexts shape the balance between these logics across diverse market economy settings. Objective: This systematic literature review addresses the question: What role do institutional contexts play in enhancing the balancing of equity and merit logic in GTM systems? The study synthesizes post-2020 peer-reviewed scholarship to develop an institutionally grounded conceptual framework explaining cross-national variation in talent system design. Method: Following PRISMA 2020 guidelines, a systematic search was conducted across four databases (Web of Science, Scopus, JSTOR, and ProQuest/ABI-Inform), yielding 3,006 total records. After deduplication, title/abstract screening, and a two-stage full-text eligibility review, a final corpus of N=50 peer-reviewed journal articles (2020–2025) was included: 17 core studies satisfying all four inclusion dimensions and 33 extended studies satisfying two or more dimensions. Studies were coded on institutional context type, dominant legitimacy logic, talent system orientation, and organizational outcomes. Findings: Four themes emerged. First, institutional context specifically the configuration of regulative, normative, and cultural-cognitive pillars (Scott, 2013) is the primary determinant of which logic prevails in GTM. Second, moral, pragmatic, and cognitive legitimacy types (Suchman, 1995) correspond systematically to equity-dominant, merit-dominant, and hybrid talent system designs. Third, hybridization reframing equity in performance terms is emerging as the dominant organizational response in institutionally pluralistic environments. Fourth, hybrid talent systems integrating moral and pragmatic legitimacy generate superior organizational outcomes. A propositional framework linking institutional context, dominant logic, talent system design, and outcomes is advanced. Conclusion: This review reframes the DEI-merit debate from ideological to institutional legitimacy analysis. Four testable propositions advance the field toward rigorous comparative empirical research. The findings carry direct implications for global HR directors, policymakers, and ESG governance teams navigating regulatory bifurcation in talent management systems globally. A Daoist meta-theoretical lens further enriches this reframing: through the principles of wu wei, yin-yang complementarity, and de, the equity-merit tension is reconceived not as a binary opposition but as a dynamic duality, positioning contextual harmony and authentic human excellence as the orienting goals of global talent systems (Hennig, 2017; Xing & Sims, 2012).